Analysis Of Social Solidarity In The Novel Argantara By Falistiyana: Literary Sociological Study - Fazlina, Sri Ayu; Qodri, Muh. Syahrul; Sapiin, Sapiin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The problem contained in this research is the form of social solidarity in the novel Argantara by Falistiyana. This research aims to describe forms of social solidarity. This research uses a literary sociology approach and this research is qualitative in nature. The data source for this research is the novel entitled Argantara by Falistiyana, published in 2022 at PT Sarana Kreasi Abadi with a thickness of 484 pages. Data collection was carried out through the literature study method, with data analysis including identifying data, classifying data, and analyzing data. The theory that is the basis of the analysis is Emile Durkheim's theory of social solidarity. Based on the results of this research, it shows that social solidarity in the Argantara novel is divided into mechanical social solidarity and organic social solidarity. Mechanical social solidarity is found in 10 data quotes, including deliberation, empathy, togetherness and the existence of repressive laws with forms of togetherness being dominant. Meanwhile, organic social solidarity is found in 8 data quotes, including appreciation, mutual respect, cooperation and the existence of restitution laws with cooperation being the dominant form.